Conceptual model for improving quality of teacher in Indonesian vocational school - Agung Panji Sasmito; Djoko Kustono; Purnomo Purnomo; Hakkun Elmunsyah (International Journal of Evaluation and Research in Education (IJERE), 2020)
Indonesia faces vocational teachers’ shortage both in the quantity and quality. One of Indonesian goverments’ effortsto overcome that problem is holding a Dual Expertise Program (DEP) to produce dual expertise teachers for vocational schools. However, the quality of dual expertise vocational teacher is still questionable. The purpose of this article is to give an idea related to the conceptual model framework for improving the quality of vocational teachers demonstrated by the teachers’ achievements. The authors of this article discuss factors that have an impact on the quality of vocational teachers and describe a framework based on a literature review that might contribute to improving the quality of vocational teachers, especially dual expertise vocational teachers. Based on the results of the article found that to improve the quality of vocational teacher can be improved through increasing self-efficacy and transferable skills, in addition to pay attention to teacher’s initial expertise and teaching experience.